2012
DOI: 10.1530/eje-11-0864
|View full text |Cite
|
Sign up to set email alerts
|

Fetuin A in nonalcoholic fatty liver disease: in vivo and in vitro studies

Abstract: Objective: Fetuin A has been associated with insulin resistance and the metabolic syndrome. We therefore explored the role of fetuin A in nonalcoholic fatty liver disease (NAFLD). Design: Cross-sectional and intervention studies. Methods: We included 111 subjects with histologically proven NAFLD of whom 44 participated in a randomized, controlled trial with metformin. One hundred and thirty-one healthy subjects and 13 subjects undergoing hepatic surgery for metastatic cancer served as controls. Main outcome va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
125
5
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 165 publications
(144 citation statements)
references
References 26 publications
11
125
5
3
Order By: Relevance
“…Fetuin-A has also been shown to correlate with liver fat in patients at risk of T2DM (Kantartzis et al, 2010). It has reported that there are a correlation between the fetuin-A gene expression and key enzymes in lipid and glucose metabolism (Haukeland et al, 2012). In our studies, γ-glutamyltransferase, ALT and AST levels were higher in type 2 diabetes when compared with control groups.…”
Section: Discussionsupporting
confidence: 64%
“…Fetuin-A has also been shown to correlate with liver fat in patients at risk of T2DM (Kantartzis et al, 2010). It has reported that there are a correlation between the fetuin-A gene expression and key enzymes in lipid and glucose metabolism (Haukeland et al, 2012). In our studies, γ-glutamyltransferase, ALT and AST levels were higher in type 2 diabetes when compared with control groups.…”
Section: Discussionsupporting
confidence: 64%
“…In some studies, hepatic fetuin-A expression and its serum levels increased in obesity and there was a strong association between the serum level of fetuin-A and liver fat accumulation (28,29). Hepatic expression of fetuin A is related to glucose and lipid metabolism (28).…”
Section: Discussionmentioning
confidence: 99%
“…In some studies, hepatic fetuin-A expression and its serum levels increased in obesity and there was a strong association between the serum level of fetuin-A and liver fat accumulation (28,29). Hepatic expression of fetuin A is related to glucose and lipid metabolism (28). Since fetuin-A is linked with fatty liver and insulin resistance, it may be considered as a new therapeutic target in NAFLD (28,29).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A pioglitazonról, metforminról, statinokról és niacinról is közölték, hogy csökkentik a fetuin-A szintjét [16,21,48,49], és ugyanez a mérsékelt alkoholfogyasztásra is igaz [44]. Fetuin-A-szintet emelő hatása az ösztrogénterápiának van [44].…”
Section: Az Ellentmondásos Eredmények Lehetséges Magyarázataiunclassified